2003
DOI: 10.1080/13102818.2003.10817062
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Some Plant Growth Regulators and Chlorsulfuron on Growth, Protein Composition and Proteolytic Activity of Maize Seedlings

Abstract: The well known inhibitory effect of abscisic acid (ABA) on growth and protein mobilization was confirmed. In general benzylaminopurine (BAP) is known as a stimulator of plant growth. However in very high concentration BAP provoked a little suppression of plant growth and of activity of some proteolytic enzymes. Irrespective of this a faster hydrolysis of storage proteins in BAP treated seeds was detected. Similar results to BAP action after N 1 -(2-chloro-4-pyridyl)-N 2 phenylurea (4PU-30) treatment were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The significant effect of CHF on seedling growth (Petkova et al 2003) correlated with the data established in the present investigations. The reduction of growth by CHF was accompanied by significant decrease in quantity of main native proteins and specific qualitative changes in electrophoretic patterns of coleoptile samples.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The significant effect of CHF on seedling growth (Petkova et al 2003) correlated with the data established in the present investigations. The reduction of growth by CHF was accompanied by significant decrease in quantity of main native proteins and specific qualitative changes in electrophoretic patterns of coleoptile samples.…”
Section: Discussionsupporting
confidence: 78%
“…ABA, BAP and 4PU-30 applied in concentrations of 500µM inhibited similarly the growth of seedlings of about 25%. CHF applied at the same concentration reduced seedling growth approximately with 75% (Petkova et al 2003). The results from the present investigation indicated that the protein quantity of bands with Rm values 0.35 and 0.50 in CHF treated coleoptiles was significantly lower compared to (LaRossa andFalko 1984, Ray 1984).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This decline is also supported by HASHEMABADI and KAVIANI (2008). This decline in the shoot length of Aloe vera might be due to the inhibitory effect of BAP, which provoke a little suppression of plant growth and activity of some proteolytic enzymes (PETKOVA et al, 2003). Rooting response of microshoots is reported to be controlled by growth regulators in the medium (BHOJWANI & RAZDAN 1992), basal salt composition (GARLAND & STOLTZ 1981, ZIMMERMAN and BROOME.1981, SKIRVIN & CHU 1979, genotype (RINES & MCCOY 1981) as well as cultural conditions (MURASHIGE 1977).…”
Section: C-value Analysesmentioning
confidence: 99%
“…Little is known about the link between ABA deficiency and proteolysis, although there are some previous results that can reinforce our assumption. For instance, ABA plays a regulatory role in maturation and germination of seeds and total proteolytic activity was inhibited by ABA in maize seedlings (Petkova et al, 2003). However, ABA displays different effects on various proteolytic activities, probably depending on its signalling pathway.…”
Section: Investigation Of Protein Degradation In Sitiensmentioning
confidence: 99%